The Impact of Online Community on Farmer Empowerment: A Technology-to-Performance Chain Approach - Anton Susanto; Ali Agus; Jangkung Handoyo Mulyo; Hakimul Ikhwan (Proceeding of International Conference on Information Science and Technology Innovation (ICoSTEC), 2022)
This research provides empirical evidence for the benefit of social media in the online farmer community. It uses the case study analysis in exploring the ICT usage in Empowerment of Laying Hens Farmer in East and Central Java implementing the multi-feed and additive supplement. The research develops The Technology-toPerformance Chain (TPC) approach and farmer empowerment model. This research use farmer empowerment as the performance impact of the online community. Meanwhile, it also predicts some factors that affect the performance impact. Those are farmer characteristics, task-technology fit, and facilitating conditions. The empowerment impacts are influenced significantly by task-technology fit with a path coefficient of 0,704. It means that utilization of social media as the online media of community will encourage empowerment if the information and knowledge sharing activities inside are related to the task or farmer's livelihood. The farmer's characteristics and the facilitating condition affect the performance insignificantly. However, the facilitating condition determines the tasktechnology fit with the path value 0,868. It means to endorse the ICT becoming fit with the task/livelihood of the farmer need the facilitating condition as the underlying factors. These factors are the internet accessibility of farmers, the innovation of the multi-nutrient and additive supplement product from socio-entrepreneurs, and the assistance/consultancy from the extension agent.